ALAT PENDETEKSI DAN PENETRALISIR ASAP ROKOK BERBASIS ARDUINO DI BENGKEL MEKAR ABADI JAYA KAB. KARAWANG - purwanto; Ponco, Catur (INFOKOM (Informatika & Komputer), 2024)
Cigarette smoke is an air pollutant that is dangerous to health. At the Mekar Abadi Jaya workshop, Kab. Karawang, cigarette smoke is a problem that often occurs. This is caused by the smoking habits of workshop workers. This research aims to develop an Arduino-based cigarette smoke detection and neutralization device. This tool consists of two main parts, namely a smoke sensor and a smoke neutralizer. Smoke sensors are used to detect the presence of cigarette smoke. If cigarette smoke is detected, the smoke neutralizer will work to neutralize the cigarette smoke. This tool has been tested at the Mekar Abadi Jaya Regency workshop. Karawang. Test results show that this tool can detect smoke and this tool can also neutralize cigarette smoke. It is hoped that this tool can help reduce exposure to cigarette smoke in the Mekar Abadi Jaya Regency workshop. Karawang. Apart from that, this tool can also be used in other places where exposure to cigarette smoke often occurs, such as factories, restaurants and other public places